2013
DOI: 10.1159/000355860
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Normal Levels of Ionized Calcium during Citrate-Based Renal Replacement Therapy Is Associated with Stable Parathyroid Hormone Levels

Abstract: Background/Aims: Citrate is an effective anticoagulant during continuous renal replacement therapy (CRRT). Previous studies showed raised parathyroid hormone (PTH) levels when aiming for serum ionized calcium [Cai] between 0.8 and 1.1 mmol/l. Our objective was to assess whether citrate-based CRRT with physiologic target systemic [Cai] between 1.12 and 1.20 mmol/l could maintain stable PTH levels. Methods: Measurement of intact PTH (PTHi) in 30 consecutive critically ill patients treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
0
8
1
Order By: Relevance
“…Our study evaluated iPTH, as well as oxPTH and noxPTH, over the first 24 h of citrate CVVH. Median baseline iPTH in our study was lower than the 264 pg/ml reported in the Van der Voort study [ 2 ], but higher than the 67 pg/ml in the study by Raimundo et al [ 3 ]. At 24 h, median iPTH in our study dropped, while it rose to 399 pg/ml in the van der Voort study and was 89 pg/ml in the Raimundo study.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Our study evaluated iPTH, as well as oxPTH and noxPTH, over the first 24 h of citrate CVVH. Median baseline iPTH in our study was lower than the 264 pg/ml reported in the Van der Voort study [ 2 ], but higher than the 67 pg/ml in the study by Raimundo et al [ 3 ]. At 24 h, median iPTH in our study dropped, while it rose to 399 pg/ml in the van der Voort study and was 89 pg/ml in the Raimundo study.…”
Section: Discussioncontrasting
confidence: 83%
“…Even a minor decrease in systemic iCa can trigger PTH release, mobilizing Ca from skeletal stores within minutes [ 7 , 8 ]. A negative Ca balance during citrate-based CRRT has been observed in three studies [ 2 , 4 , 5 ], and in two a rise in intact (i)PTH has been reported [ 2 , 3 ]. Although it seems rational to replace the lost amount of Ca, in clinical practice Ca replacement is often adjusted to the systemic iCa concentration, despite the fact that the optimal iCa concentration during critical illness is not known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative Ca balance and systemic hypocalcemia in citrate CVVH can lead to further activation of parathormone (PTH) which may already have been activated due to renal dysfunction [25,28,32]. Van der Voort found that median systemic iPTH was significantly higher in the citrate group (iCa at 0.8-1.0 mmol/l) compared to both the nadroparin group and the control group without renal failure [25].…”
Section: Hormonal Effects Of Citratementioning
confidence: 99%
“…Targeting a higher plasma calcium concentration seems to suppress PTH release, which may limit calcium mobilization from bone. However, PTH measurements in critically ill patients should be interpreted with caution, because the normal assay measures oxidized PTH as well, which is biologically inactive [ 22 ]. Some modern CRRT devices incorporate an algorithm with a 100 % calcium compensation option, which seems attractive.…”
Section: Calciummentioning
confidence: 99%